Bahasa dan Gender dalam Sinetron Malaysia "Melur Untuk Firdaus" - Pujasari, Norma Sarah; Widayati, Wahyu (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2023)
Soap operas are serial plays with conflicts between characters in them. In the past, soap operas could only be enjoyed on television. However, now soap operas can be accessed via mobile phones according to the wishes of the owner. The Malaysian soap opera entitled "Melur untuk Firdaus" which is the object of research tells the story of the matchmaking of a pair of lovers with different language features between the languages used by women and men. Therefore, the characteristics of the language in this soap opera are studied and related to gender. This research is qualitative descriptive research. Data collection was carried out using the see method. The technique used is tapping and free listening techniques. The data analysis used is textual analysis. The results of the study show that the female characters in the soap opera "Melur for Firdaus" have the linguistic characteristics proposed by Lakoff, namely hedge, tag question, intensifier, empty adjectives, avoidance of strong swear words and high-pitched intonation. Not only do women use these features, the men in the soap opera also use language features or characteristics that should only be used by women. For example, tag questions, avoidance of strong swear words and high-pitched intonation. Along with the development of the times, men and women have equality, so that the features or characteristics of language also follow its development and are no longer the same as before. Even so, not all of the characteristic features of women's language are also used by men.Keywords: language; gender; soap operaAbstrakSinetron adalah tayangan sandiwara bersambung dengan konflik antartokoh di dalamnya. Dulu sinetron hanya dapat dinikmati melalui televisi. Akan tetapi, sekarang sinetron dapat diakses melalui telepon genggam sesuai kemauan pemiliknya. Sinetron Malaysia berjudul "Melur untuk Firdaus" yang menjadi objek penelitian berkisah tentang perjodohan sepasang kekasih dengan fitur bahasa yang berbeda antara bahasa digunakan oleh perempuan dan laki-laki.  Oleh karena itu, karakteristik bahasa dalam sinetron ini dikaji dan dikaitkan dengan gender.  Penelitian ini adalah penelitian deskriptif kualitatif. Pengumpulan data dilakukan dengan metode simak. Teknik yang digunakan yaitu teknik sadap dan simak bebas cakap. Analisis data yang digunakan adalah analisis tekstual. Hasil penelitian menunjukkan bahwa tokoh perempuan dalam sinetron "Melur untuk Firdaus" memiliki karakteristik kebahasaan yang dikemukakan oleh Lakoff yakni hedge, tag question, intensifier, empty adjectives, avoidance of strong swear words, dan intonasi berbicara dengan nada tinggi. Tidak hanya perempuan yang menggunakan fitur tersebut, laki-laki dalam sinetron tersebutÂ  juga menggunakan fitur atau karakteristik bahasa yang seharusnya hanya dipakai perempuan. Misalnya tag question, avoidance of strong swear words, dan intonasi berbicara dengan nada tinggi. Seiring berkembangnya zaman, laki-laki dan perempuan memiliki kesetaraan, sehingga fitur atau karakteristik bahasa pun mengikuti perkembangannya dan tidak lagi sama dengan masa sebelumnya. Meskipun demikian, tidak seluruh fitur karakteristik kebahasaan perempuan juga digunakan laki-laki.Kata kunci: bahasa; gender; sinetron